PELAKSANAAN GADAI KONVENSIONAL DAN GADAI SYARIAH (STUDI PADA PT.PEGADAIAN CABANG GAHARU MEDAN DAN PT.PEGADAIAN SYARIAH CABANG SETIA BUDI MEDAN) - ZUHRIATI KHALID (PREMISE LAW JURNAL, 2018)
DOSEN PEMBIMBING:1. M. Hasballah Thaib2. Muhd Yamin3. Idha Aprilyana Sembiring Man is a social being (zoon politicon) and economic being (homo economicus) so that they need to one another, particularly fulfilling their economic needs. One of the implementations of fulfilling the economic needs is by pawning at PT. Pegadaian, either conventional and sharia. Conventional and Sharia Pawn Shop is the pawn which has legal concepts which are different from one to another, from legal principle, legal sources, and its operational technique. However, the differences are not the obstacle for the people. It can be seen from the enthusiasm of the Moslems and non-Moslems who participate in doing pawning transaction, either in the Conventional Pawn Shops or in Sharia Pawn Shops.Keywords: Implementation, Conventional Pawn, Sharia Pawn